Virus-Induced Cytoplasmic Membrane Structures Associated with Semliki Forest Virus Infection Studied by the Freeze-Etching Method - Virtanen, Ismo (1974)
Intracellular membrane structures associated with the Semliki Forest virus replication process were studied from freeze-etch replicas. Cleaved membrane structures inside the CPV I type vacuoles lacked the typical membrane particles present on most other fractured membranes. CPV II type vacuoles present in thin sections were obscured in the freeze-etch replicas by the cytoplasmic ground substance.